The relationship between family support and the activeness of elderly posyandu visits in Puton Village - Tri Widiasari; Fitri Firranda Nurmalisyah (Journal of Clinical Nursing Studies and Practice, 2026)
The annual increase in the elderly population is often accompanied by a decline in their health status, creating functional limitations that can restrict their attendance at the integrated health post (Posyandu), though such limitations can be minimized through adequate family support. Therefore, this study aimed to determine the relationship between family support and the attendance of the elderly at Posyandu in Puton Village, Diwek District, Jombang Regency. Using a correlational analytical research design with a retrospektif approach, the study involved a population of 121 respondents, from which a sample of 93 respondents was selected via a simple random sampling technique. The findings revealed that almost all (96.8%) of the elderly received family support and actively attended Posyandu visits, whereas a small percentage (3.2%) remained active despite receiving unsupportive family care. Statistical analysis using the alternative Fisher’s exact test yielded a p-value of 0.000 (p < 0.05), thereby accepting H1 and confirming a significant relationship between family support and elderly Posyandu attendance. In conclusion, while family support plays a critical role in encouraging attendance, low attendance and a lack of support are not necessarily adverse outcomes, but may instead reflect a shifting phenomenon driven by a trend of better health status among elderly individuals who are highly educated, employed, and earn equal to or greater than the Regional Minimum Wage (UMK).